The Influence of CEO’s Demographic Characteristics on Tax Aggressiveness in Family Firm - Dwi Astutik; Lintang Venusita (Jurnal Akuntansi dan Keuangan, 2020)
This research aims to analyze how the educational background, tenure, and gender of Chief Executive Officer (CEO) affect tax aggressiveness in a family firm. Independent variables comprise the educational background, tenure, and gender of CEO while tax aggressiveness plays as dependent variable. In addition to those three parameters, the controlled variable also includes leverage and profitability. Population and sample of this research were taken from family firms registered in the Indonesian Stock Exchange during 2013 - 2016. With the purposive sampling, the number of total samples and sampling units in this research are 42 and 168, respectively. Furthermore, documentation techniques manifested in financial statement and annual report are used as data collection method where panel data regression with a fixed effect model is employed for statistical analysis. The present results demonstrate that the educational background and profitability significantly give a negative effect on the tax aggressiveness whereas the tenure and leverage considerably contribute to a positive consequence in the tax aggressiveness. Interestingly, it is shown that the gender factor does not substantially influence the tax aggressiveness.